Effectiveness of Rosmarinus officinalis for Androgenetic Alopecia: A Literature Review - Cintantya Prakasita; Desak Nyoman Trisepti Utami; Natasha Caroline Gigir; Ni Ketut Putri Ratih Sindunata (International Medical Journal Corp. Ltd, 2025)
Androgenetic alopecia (AGA), also known as androgenic alopecia or male pattern baldness, is the most common type of progressive hair loss.. Androgenetic alopecia is hereditary and is transmitted through an autosomal dominant genetic pattern. This genetic predisposition is directly associated with androgen hormones, in which androgens induce miniaturization of hair follicles on the scalp and a progressive shortening of the anagen phase in the hair cycle. There are evidence-based therapeutic interventions for androgenetic alopecia, including both pharmacological and non-pharmacological approaches. The 5α-reductase inhibitors, finasteride and dutasteride, effectively suppress dihydrotestosterone (DHT) synthesis but are associated with sexual dysfunction including erectile dysfunction, reduced libido, and ejaculatory disorder as well as gynecomastia. Androgen receptor antagonists such as spironolactone may induce postural hypotension and hyperkalemia, cyproterone acetate carries risks of mood disturbances and hepatotoxicity, and flutamide is linked to dose-dependent severe hepatic injury. This literature review explores the therapeutic potential of herbal remedies Rosmarinus Officinalis known for their anti inflammatory agent, anti androgenic agent, anti fungal agent, photoprotective agent, and a vasodilator. This review emphasizes the potential and effectiveness of Rosmarinus Officinalis in advancing dermatological care and providing effective, plant-based solutions for Androgenetic Alopecia with minimal side effects.